The effect of green supply chain management practices on environmental performance and competitive advantage: a case study of the cement industry - Khaksar, Ehsan; Abbasnejad, Tayyebeh; Esmaeili, Ahmad; Tamošaitienė, Jolanta (Technological and Economic Development of Economy, 2016)
Nowadays, sustainable development has been introduced and integrated into production and operation management field through the concept of the green supply chain. Green regulations and principles have gained the interest of managers and practitioners in selecting innovative practices for suppliers and organisations. Accordingly, the present study aims to evaluate the relationship between a green supplier, green innovation, environmental performance, and competitive advantage in the cement industry, which is an important industry for Iran. This study is descriptive in nature and conducted based on correlation and structural equation modelling. Managers and experts of cement companies in Fars Province are selected as samples for the study. A questionnaire and Smart-PLS software were used as research tools. The results of data analysis show that there is a positive and significant relationship between a green supplier, green innovations and environmental performance of an organisation, while there is a negative yet significant relationship between a green supplier, green innovations and environmental performance of an organisation. There is also a significant positive relationship between green innovation and environmental performance on one hand, and environmental performance and competitive advantage on the other.First published online: 01 Nov 2015